2017
DOI: 10.1111/polp.12192
|View full text |Cite
|
Sign up to set email alerts
|

Which Candidates Can Be Mavericks? The Effects of Issue Disagreement and Gender on Candidate Evaluations

Abstract: As approval ratings of the U.S. Congress remain depressed, many candidates present themselves as mavericks, willing to counter their party on issues. Yet disagreeing with one's party can be a risky decision and one that is not equally viable for all politicians. In particular, female candidates often face a hostile political climate that privileges “masculine” traits over feminine traits, which may tie female candidates to their party's platform. An experimental study manipulating issue disagreement for a fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 47 publications
(99 reference statements)
1
9
0
Order By: Relevance
“…These studies assume that masculine stereotypes will benefit female candidates, but our findings suggest otherwise. Our finding that female candidates face a backlash for emphasizing masculine qualities fits with other research showing that counter-stereotypic female candidates face a backlash (Bauer 2017; Bauer, Harbridge, & Krupnikov 2017; Krupnikov and Bauer 2014; Vraga 2017). Our outcome measures focus on perceptions of issue competencies, but future research measuring perceptions of candidate trait attribution can offer more insight into why masculine visuals reduce the perceived viability of female candidates.…”
Section: Discussionsupporting
confidence: 90%
“…These studies assume that masculine stereotypes will benefit female candidates, but our findings suggest otherwise. Our finding that female candidates face a backlash for emphasizing masculine qualities fits with other research showing that counter-stereotypic female candidates face a backlash (Bauer 2017; Bauer, Harbridge, & Krupnikov 2017; Krupnikov and Bauer 2014; Vraga 2017). Our outcome measures focus on perceptions of issue competencies, but future research measuring perceptions of candidate trait attribution can offer more insight into why masculine visuals reduce the perceived viability of female candidates.…”
Section: Discussionsupporting
confidence: 90%
“…This experiment only tested the influence of positive masculine traits that reflect the qualities voters desire in political leaders. Female candidates may receive more pushback if they engage in masculine strategies that do not fit with the expectations voters have for good leadership such as airing negative ads or defying party leaders (Bauer et al 2017; Krupnikov and Bauer 2014; Vraga 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This result comports with the urban politics literature which contends that many of the issues and responsibilities of local offices reflect masculine stereotypic strengths. The positive role of masculinity in evaluations of female candidates also clarifies a debate in the literature on gender stereotyping which offers conflicting findings about whether masculinity benefits (Bauer 2017; Brooks 2013; Holman et al 2016; Holman, Merolla, and Zechmeister 2017) or harms female candidates (Bauer, Harbridge, and Krupnikov 2017; Krupnikov and Bauer 2014; Vraga 2017). Third, I show that candidate sex, partisan identities, and gender stereotypes interact in unique ways at the local level.…”
mentioning
confidence: 82%
“…Levi and Stoker (2000) conclude that trust in individual politicians, albeit on the decline, still plays a role in citizens' judgments and decision-making processes (see also Bittner, 2015). It has also been shown that trait perceptions of this kind are associated with gendered stereotypes (e.g., Bauer, 2017;Huddy & Terkildsen, 1993;Vraga, 2017). In addition, Chen, Jing, and Lee (2013) provide empirical support for the claim that while both character (i.e., trustworthiness) and competence do matter in citizen judgments of politicians, competence is a necessary, but not sufficient, condition for trustworthiness to have a meaningful impact.…”
Section: Predicting Political Supportmentioning
confidence: 97%